Spatio-genetically coordinated TPR domain-containing proteins modulate c-di-GMP signaling in Vibrio vulnificus. - Shobnom Mustaree; Ram Podicheti; Doug Rusch; Dean A Rowe-Magnus (PLoS Pathogens, 2025)
Vibrio species, which include several pathogens, are autochthonous to estuarine and warm coastal marine environments, where biofilm formation bolsters their ecological persistence and transmission. Here, we identify a bicistronic operon, rcbAB, whose products synergistically inhibit motility and promote biofilm maturation post-attachment by modulating intracellular c-di-GMP levels in the human and animal pathogen V. vulnificus. RcbA contains an N-terminal tetratricopeptide repeat (TPR) domain and a structured C-terminal region of unknown function, while RcbB possesses an N-terminal TPR domain and a C-terminal GGDEF domain characteristic of diguanylate cyclases. The TPR domain of RcbB represses its diguanylate cyclase activity, while RcbA's TPR domain and C-terminal region co-operatively de-repress it. Localization of both proteins to the flagellar pole is TPR-dependent but not co-dependent, although RcbA anchors RcbB to the pole in the absence of polar landmarks such as HubP and flagella. The conservation of rcbAB across diverse bacterial taxa substantiates its fundamental importance in bacterial biology. This work demonstrates how spatio-genetically coordinated TPR domain-containing proteins modulate c-di-GMP signaling, contributing to our understanding of biofilm formation in Vibrio species and potentially other bacteria. It also reveals the first evidence of inter-protein interaction via the TPR domains of both partners, challenging the conventional paradigm in which only one bears the domain.